Impact of Dividend Policy on Share Price Valuation in Nigerian Banks - Duke, Stephen Bassey; Nneji, Ikenna Dominic; S. E., Nkamare (Archives of Business Research, 2015)
This study investigated the impact of dividend policy on share price valuation in Nigerian banks. This was done by utilising data on two banks operating in the Nigerian economy (GTBank and United Bank for Africa). The data used for this study are market price, dividend yield and retention ratio. Market price was the dependent variable while dividend yield and retention ratio were included in the independent variables. In order to accomplish the set out objectives of this study, two research hypotheses (Ho1 - Ho2) were formulated which were tested via a number of analytical techniques. These are the ADF Unit Root Test and the ordinary least squares test. These tests were carried out with the aid of e-views software package. Based on the results gotten, the null forms of both hypotheses were rejected while the alternate forms were accepted. The results revealed that dividend yield had a significantly positive effect on share price while retention ratio was found to have a significantly negative effect on it. The study ended by giving recommendations which include: Banks should ensure that they have an optimal robust dividend policy in place. Regular update of records of shareholders should be made to avoid a deliberate diversion or undue retention of unclaimed dividend warrants. Government should set up a body that will help to manage unclaimed dividends and also ensure that situations that give rise to such are minimized Keywords: Share-price, Dividend Policy, Dividend yield, Retention ratio